Circulating immune cells and apolipoprotein A mediation: a Mendelian randomization study on hypertensive disorder of pregnancy - Liu, Jingting; Zhou, Yawei; Dong, Yijun; Wang, Wendi; Li, Yan; Pei, Jianying (Frontiers in Immunology, 2024)
Background Studies using observational epidemiology have indicated that inflammation and immunological dysregulation are important contributors to placental and renal failure, which ultimately results in maternal hypertension. The potential causal relationships between the immunophenotypes and hypertensive disorder of pregnancy (HDP) are yet unclear.We conducted two-sample Mendelian randomization (MR) analyses to thoroughly examine the relationship between immunophenotypes and HDP. The GWAS data on immunological traits was taken from public catalog for 731 immunophenotypes and the summarized GWAS data in 4 types of HDP were retrieved from FinnGen database. The link between immune cell traits and HDP was examined through our study methodology, taking into account both direct relationships and mediation effects of apolipoprotein A (apoA). The inverse variance weighted (IVW) method served as the main analysis, while sensitivity analysis was carried out as a supplement.We identified 14 highly correlative immunophenotypes and 104 suggestive possible factors after investigating genetically predicted immunophenotype biomarkers. According to the IVW analysis, there was a strong correlation between HDP and HLA DR on DC and plasmacytoid DC. Reverse MR analysis showed that there was no statistically significant effect of HDP on immune cells in our investigation. Mediation analysis confirmed that apoA mediates the interaction between HLA DR on DC and HDP.2 Conclusion Our results highlight the complex interplay of immunophenotypes, apoA, and HDP. Moreover, the pathophysiological link between HLA DR on DC and HDP was mediated by the level of apoA.